Surgical excision of benign spindle cell neoplasm of the cervix predating miscarriage due to cervical insufficiency: A case report - Ntsako Nkanyane; Nnabuike Chibuoke Ngene (Elsevier, 2022)
This case report is on cervical spindle cell neoplasm and complications of its excision. A 34-year-old multiparous woman presented with a one-year history of mild to moderate non-radiating lower abdominal pain and a sensation of a mass in the vagina when urinating. These symptoms were associated with a recurrent foul-smelling yellow vaginal discharge which was unresponsive to antibiotic therapy prescribed at a primary healthcare clinic. Vaginal examination at a gynaecological clinic revealed a firm circular cervical mass. Excision biopsy of the mass (attached between the 1 and 3 o'clock positions on the cervix) showed a benign spindle cell neoplasm. The patient became pregnant six months after the surgical excision and had a miscarriage at 18 weeks of gestation due to cervical insufficiency. The report highlights the importance of antenatal surveillance for women following surgical excision of a cervical lesion such as spindle cell neoplasm as they may be predisposed to cervical insufficiency.